Change in Mallampati class during labor: Hypertensive versus normotensive parturients. Issue 8 (22nd May 2018) - Raza, D.; Ismail, S.
Abstract : Background: Mallampati class has been shown to increase during labor. There are no prospective studies evaluating airway changes in hypertensive parturients during labor. The aim of our study was to observe the frequency of change in Mallampati class during labor in hypertensive compared to normotensive parturients. Methods: In this prospective observational cohort study, 60 parturients were enrolled and divided into two groups of 30 each: hypertensive parturients and normotensive parturients. The Mallampati class was evaluated in each parturient at two points; during early labor (cervical dilation 1‐3 cm and regular contractions) taken as T1 and at 20 minutes after delivery taken as T2. The change in Mallampati class from T1 to T2 was compared between the two groups. Post‐stratification chi‐square test was applied and P value <.05 was considered as significant. Results: The change in Mallampati class was significantly more frequent in hypertensive group as compared to normotensive group [80% (24/30) vs 46.7% (14/30); P  = .002]. Overall, an increase in Mallampati class during labor was found with statistically significant difference between the hypertensive and normotensive group [80% (24/30) vs 42.9% (12/28); P  = .004]. The risk of increase in Mallampati class was 2 times higher in hypertensive women as compared to normotensive 2.44; 95% CI: 1.19 to 5.02]. Conclusion: Mallampati class showed 2‐fold increase in hypertensive compared to normotensive parturients during labor; requiring additional caution during airway management.